2017
DOI: 10.1590/1678-77572016-0230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NiTi alloy on the root canal shaping capabilities of the ProTaper Universal and ProTaper Gold rotary instrument systems

Abstract: Objective This study aimed to evaluate the influence of the NiTi wire in Conventional NiTi (ProTaper Universal PTU) and Controlled Memory NiTi (ProTaper Gold PTG) instrument systems on the quality of root canal preparation.Material and Methods Twelve mandibular molars with separate mesial canals were scanned using a high-definition microcomputed tomography system. The PTU and PTG instruments were used to shape twelve mesial canals each. The canals were scanned after preparation with F2 and F3 instruments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
1
28
1
3
Order By: Relevance
“…In addition, heat‐treated instruments tend to have a greater centring ability than conventional NiTi alloys (Duque et al . , Ozyürek et al . , Bürklein et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, heat‐treated instruments tend to have a greater centring ability than conventional NiTi alloys (Duque et al . , Ozyürek et al . , Bürklein et al .…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturers have introduced several modifications in design and alloy NiTi instruments to improve their mechanical properties and safety during root canal preparation, mainly in curved canals (Duque et al . , Alcalde et al . , Bürklein et al .…”
Section: Discussionmentioning
confidence: 99%
“…) and the ProTaper Gold system (Elnaghy & Elsaka , Duque et al . ), which are manufactured by the conventional machining method. Further studies are necessary for a better understanding of the behaviour of this instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the manufacturing method on the cutting power of the instruments was not evident because in the apical and cervical region, there was statistical similarity between the Hyflex EDM system produced by electroerosion (Iacono et al 2017) and the ProTaper Gold system (Elnaghy & Elsaka 2016, Duque et al 2017, which are manufactured by the conventional machining method. Further studies are necessary for a better understanding of the behaviour of this instrument.…”
Section: Discussionmentioning
confidence: 99%
“…, Duque et al . ) and concluded that the more flexible NiTi alloys favoured less canal transportation.…”
mentioning
confidence: 99%